GROWTH AND PHYSIOLOGICAL RESPONSES OF WHEAT CULTIVARS UNDER VARIOUS PLANTING WINDOWS - M. Ahmed; S. Farooq (Journal of Animal and Plant Sciences, 2013)
The accumulated photothermal units, growth attributes and phenology of three wheat varieties (Chakwal-50, Wafaq-2001 and an advance line NR-268) were studied in four planting windows from 20th October-5th December at 15 days interval during 2008-09 in Randomized Complete Block Design with factorial arrangements. Delayed sowing puts adverse effects with respect to growth characteristics of tested varieties like Crop growth rate (CGR), Net assimilation rate (NAR), Leaf area index (LAI) and growing degree days and photothermal units but the intensity varied among varieties. The late sown conditions induced the maximum epicuticular wax deposition (0.0071 g cm-2) and synthesis of proline contents (37.08 µg g-1) in leaf tissues at flag leaf stage and it was typically related to Chakwal-50 (44.45 µg g-1). The Wafaq-2001 did well with respect to stomatal conductance and photosynthetic rates over tested NR-268 even in delayed sowing. Sustaining the growth in late sown conditions of Wafaq-2001 was clear indication of its adoptability measures to terminal heat stress. On overall basis, the Chakwal-50 was the best performer and seeding at 5th November must be ensured to maintain desirable growth pattern. The growing degree days and Photothermal units were growth drivers and early sowing time might need to be changed based on concept for better understanding of phenophases and other growth aspects of crop in context of climate variability.
Keywords: Phenology; Planting windows; Crop growth rate; Net assimilation rate; Leaf area index; Photothermal units